Spectral Decomposition with Continuous Wavelet Transform for Hydrocarbon Zone Detection of North Bali Waters - Tumpal Bernhard Nainggolan; Muh. Nur Iqlal Manai; Subarsyah Subarsyah (Marine Geological Institute of Indonesia, 2018)
The East Java Basin is developed from an oceanic basin in front of Late Cretaceous Java Trench subduction zone to presently back-arc basin behind the Java-Lombok volcanic arc to the south. Many studies conclude hydrocarbon discovery in deep carbonate Ngimbang Formation. However, as a result of the active tectonic history of the region, there are fractures from Ngimbang Formation upward to the Oligo-Miocene Kujung Formation. It developes enhanced permeability medium for a good hydrocarbon migration. This paper presents shallow gas detection zone in the Mundu Formation by applying the spectral decomposition method with continous wavelet transform. Spectral decomposition can be effectively used to identify hydrocarbon reservoirs by analyzing seismic data in the frequency domain. Spectral decomposition with frequency 20 Hz shows the potential zone at time 779 - 832 ms which is suitable with depth 2237.5 - 2355.6 feet in well TRG-1. This method is supported with quantitative calculation of petrophysical analysis that determines 5 pay flag zones range from 2208.5 feet until 2347.5 feet.Keywords : East Java Basin, spectral decomposition, continuous wavelet transform, petrophysical analysisCekungan Jawa Timur terbentuk dari cekungan samudera di tepi zona subduksi pulau Jawa pada masa Cretaseous/Kapur Akhir hingga cekungan busur belakang sistem vulkanik Jawa-Lombok di selatan. Banyak penelitian menyimpulkan penemuan hidrokarbon pada lapisan karbonat Formasi Ngimbang yang dalam. Namun, sebagai akibat dari sejarah tektonik aktif dari wilayah tersebut, terdapat rekahan dari Formasi Ngimbang sampai ke atas hingga Formasi Kujung pada masa Oligo-Miosen. Kejadian tersebut menyebabkan timbulnya peningkatan permeabilitas medium yang baik untuk migrasi hidrokarbon. Makalah ini menyajikan deteksi zona gas dangkal pada Formasi Mundu dengan menerapkan metode dekomposisi spektral dengan transformasi wavelet kontinyu. Dekomposisi spektral dapat secara efektif digunakan untuk mengidentifikasi reservoir hidrokarbon dengan menganalisa data seismik dalam domain frekuensi. Dekomposisi spektral dengan frekuensi 20 Hz menunjukkan zona potensial pada kedalaman domain waktu 779 - 832 ms yang sesuai dengan 2237.5 - 2355.6 kaki pada sumur TRG-1. Metode ini didukung dengan perhitungan kuantitatif analisa petrofisika yang menentukan 5 zona gas mulai dari 2208.5 kaki hingga 2.347.5 kaki.Kata kunci : Cekungan Jawa Timur, dekomposisi spektral, transformasi wavelet kontinyu, analisa petrofisika